PENGARUH TUTOR SEBAYA TERHADAP PRESTASI BELAJAR MATA PELAJARAN MEKANIKA KELAS X TGB DI SMK NEGERI 1 BATIPUH TANAH DATAR - Rahmat Nuryanto Putra; Drs. Revian Body, MSA (CIVED, 2019)
Abstract— The background of this research is the lowing of mechanic’s achievement students at class X TGB of SMKN 1 Batipuh. The purpose of this research is to reveal the influence application of peer tutor toward students’ achievement in mechanic subject at class X TGB SMKN 1 Batipuh. This research is designed as an experimental research in Pretest-posttest control group design. The sample is taken totally at class X TGB and the analysis is taken by using T-test. The result of this research reveals there is a significance influenceof application peer tutor toward mechanic’ achievement students at class X TGB in SMKN N 1 Batipuh. The conclusion shows that there is increasing of students’ achievement in experimental class than control class. Keywords: The Influence, Peer Tutor, Learning Achievement